Association of salivary pH in patients with dental caries and periodontal disease - Joshi, Astha; Gupta, Ankita; Lihala, Ratika; Vaid, Pulkit (International Journal of Research in Medical Sciences, 2021)
Background: The aims of the study was to find out the prevalence of dental caries in healthy and periodontal disease and its association with salivary pH. Methods: A total of 80 healthy subjects reporting to the department of periodontology were selected. They were divided into four groups (clinically healthy gingival, chronic generalized gingivitis, chronic generalized periodontitis, and aggressive periodontitis) with 20 subjects in each. Periodontal parameters; decayed, missing, and filled teeth (DMFT) index and salivary pH were recorded. Unstimulated whole saliva was collected according to Navazesh method. The pH of saliva was immediately measrued using a single electrode digital pH meter. Results: Based on statistical test it was seen that caries prevalence and DMFT was found out to be least in aggressive periodontitis group, along with least mean pH value, as compared to the other 3 groups, p<0.05. Conclusions: The low prevalence of caries in aggressive periodontitis can be attributed to the low pH of saliva. Salivary pH plays a vital role in the formation of microbial film, which in turn has a significant role in the pathogenesis of both dental caries and periodontitis.